METHODICAL APPROACH TO THE COST OPTIMIZATION FOR DELIVERY OF EXPECTED MATERIAL-TECHNICAL MEANS TO CONSUMER WITH TAKING ACCOUNT THEIR OPPORTUNENESS OF DELIVERY - Ihor V. Stupnytskyi (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni, 2018)
The article is devoted to the development of a methodical approach to minimizing the cost of material-technical means (MTM)transporting  from several suppliers to several consumers of these means, taking into account such an indicator of the effectiveness of the logistics system of troops, as the delivery opportuneness of material-technical means (missiles and ammunition , fuel and lubricants, military-technical property, foodstuffs, etc.) to troops during the operation (combat actions) by vehicles of a certain type. The article analyzes the existing methods of substantiation of the requirements for troop transport support during the operation (combat actions), qualifies their defects. The research examines the scheme of providing troops with expendable MTM, in which several suppliers provide several consumers of material and technical means. At the same time, the availability of MTM stocks from suppliers and the need for consumers is the source of this article. To resolve the issue of optimizing the costs of material and technical means delivering from suppliers to consumers, an optimization task is formulated and solved, conditions-restrictions are defined, which should be taken into account during the calculations.